2014
DOI: 10.1007/s13197-014-1402-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 24-epibrassinolide treatment on the metabolism of eggplant fruits in relation to development of pulp browning under chilling stress

Abstract: This study aims to investigate the effect of 24-epibrassinolide (EBR) on the metabolism in relation to development of chilling injury-induced pulp browning of eggplant fruit. The fruits were dipped for 10 min in solutions containing 10 μmM EBR and then stored at 1°C for 15 days. Chilling injury index, weight loss, electrolyte leakage and malondialdehyde (MDA) content of control fruit increased during storage. Chilling injury improved phenylalanine ammonia-lyase (PAL), polyphenol oxidase (PPO), and peroxidase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 42 publications
(49 reference statements)
2
24
0
Order By: Relevance
“…Wang et al [ 160 ] showed that BRs mitigate the action of CI in green bell peppers, accompanied by a reduction in electrolyte leakage, a reduction MDA content, and enhanced the activity of antioxidant enzymes such as CAT, APX, and GR. In the same way, Gao et al [ 161 ] have found that BR alleviated CI and flesh browning in eggplant fruit maintaining membrane integrity and moisture content, by declining in the accumulation of H 2 O 2 and by inducing total phenolics and PAL, PPO, and POD activities.…”
Section: Postharvest Treatments That Reduce Oxidative Stress and Cmentioning
confidence: 83%
“…Wang et al [ 160 ] showed that BRs mitigate the action of CI in green bell peppers, accompanied by a reduction in electrolyte leakage, a reduction MDA content, and enhanced the activity of antioxidant enzymes such as CAT, APX, and GR. In the same way, Gao et al [ 161 ] have found that BR alleviated CI and flesh browning in eggplant fruit maintaining membrane integrity and moisture content, by declining in the accumulation of H 2 O 2 and by inducing total phenolics and PAL, PPO, and POD activities.…”
Section: Postharvest Treatments That Reduce Oxidative Stress and Cmentioning
confidence: 83%
“…The results showed that, after 5 days of storage, 1% chitosan and CaP + Chit had higher lightness values than the control slices. Moreover the lower L * indicates more browning . These measures were reflected in the subjective observations made by assessing the browning index.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover the lower L * indicates more browning. 28 These measures were reflected in the subjective observations made by assessing the browning index. These results are comparable with those of Saba and Sogvar 29 who reported a lower browning index for fresh-cut apple coated with carboxymethyl cellulose-based coatings compared to untreated control slices.…”
Section: Browningmentioning
confidence: 99%
“…Chilling is known to stimulate physiological changes such as loss of firmness, fresh weight and color, and a high respiration rate (Carvajal et al, 2011;Wang et al, 2007). Chillinginduced browning due to oxidation of phenolics by the activity of PPO has been reported in basil (Wongsheree et al, 2009) and eggplant (Gao et al, 2015).…”
Section: Introductionmentioning
confidence: 99%